Reduced Water Negatively Impacts Social Bee Survival and Productivity Via Shifts in Floral Nutrition. Issue 5 (6th October 2020) - Wilson Rankin, Erin E; Barney, Sarah K; Lozano, Giselle E
Abstract: Pollinators provide a key ecosystem service vital for the survival and stability of the biosphere. Identifying factors influencing the plant–pollinator mutualism and pollinator management is necessary for maintaining a healthy ecosystem. Since healthy beehives require substantial amounts of carbohydrates (nectar) and protein (pollen) from forage plants such as clover, we must assess how resources offered by plants change under limited water conditions in order to fully understand how drought modifies the pollination mutualism. Here we document how reduced water availability leads to decreased nectar quality and quantity and decreased protein quality of pollen. Furthermore, we provide conclusive evidence that these lower quality resources lead to decreased survival and productivity in both developing honey bees (Hymenoptera: Apidae) and bumble bees (Hymenoptera: Apidae). The results emphasize the importance of the nutritional effects of reduced water on bees when predicting shifts of pollination mutualisms under climate change.